Strategic marketing analysis for enhancing competitiveness and customer satisfaction: a case study of Indihome TV in Pasuruan City - Hilmi, Muhammad Hafidh Syauqil; Zunaidi, Rizqa Amelia; Wulandari, Eka Devi (Universitas Mercu Buana, 2025)
This study aims to develop effective marketing strategies for Indihome TV to enhance its competitiveness and customer satisfaction in Pasuruan City. Utilizing a comprehensive approach, the research integrates tools such as the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, SWOT analysis, Boston Consulting Group (BCG) Matrix, and Quantitative Strategic Planning Matrix (QSPM). Eleven alternative strategies were identified, of which five were prioritized: conducting targeted marketing campaigns emphasizing ease of access to entertainment, increasing the frequency of discounts, offering economical subscription packages, providing flexible channel selection options, and rewarding loyal customers.The results highlight the significance of addressing customer concerns, particularly pricing and convenience, to improve brand recognition and attract a wider audience. Key strategies such as promoting tailored packages and enhancing customer loyalty through discounts and bonuses are designed to align Indihome TV’s offerings with customer needs. The Pareto Chart analysis confirmed that these top five strategies account for over 50% of the company’s potential improvement in marketing outcomes.These findings provide a strategic roadmap for Indihome TV to strengthen its market position, improve customer retention, and achieve sustainable growth. This research emphasizes the importance of aligning marketing strategies with internal strengths and external opportunities to address competitive pressures effectively.